Enzymatically promoted release of organic molecules linked to magnetic nanoparticles - Lambruschini, Chiara; Villa, Silvia; Banfi, Luca; Canepa, Fabio; Morana, Fabio; Relini, Annalisa; Riani, Paola; Riva, Renata; Silvetti, Fulvio (Beilstein Journal of Nanotechnology, 2018)
Magnetite-based magnetic nanoparticles have been successfully coupled to an organic system constituted of a fluorescent molecule, a tripeptide specifier and a spacer. The system is able to selectively release the fluorescent molecule upon targeted enzymatic hydrolysis promoted by a lysine/arginine specific protease.
Keywords: drug delivery; enzyme catalysis; magnetic nanoparticles; magnetic properties; peptides